Socio-economic aspects of agro-pastoral production systems in the Niono and Live Delta region in Mali - Lewis, J.V.D. (International Livestock Centre for Africa, 1978)
A preliminary working paper to help in the identification and analyses of the agro-pastoral systems, and constraints within those system, which are currently under examination within the ILCA study zone in Mali.